Harnessing Finger Millet to Combat Calcium Deficiency in Humans: Challenges and Prospects - Puranik, Swati; Kam, Jason; Sahu, Pranav P.; Yadav, Rama; Srivastava, Rakesh K.; Ojulong, Henry; Yadav, Rattan (Frontiers in Plant Science, 2017)
Humans require more than 20 mineral elements for healthy body function. Calcium (Ca), one of the essential macromineral, is required in relatively large quantities in the diet for maintaining a sound overall health. Young children, pregnant and nursing women in marginalized and poorest regions of the world, are at highest risk of Ca malnutrition. Elderly population is another group of people most commonly affected by Ca deficiency mainly in the form of osteoporosis and osteopenia. Improved dietary intake of Ca may be the most cost-effective way to meet such deficiencies. Finger millet [Eleusine coracana (L.) Gaertn.], a crop with inherently higher Ca content in its grain, is an excellent candidate for understanding genetic mechanisms associated with Ca accumulation in grain crops. Such knowledge will also contribute toward increasing Ca contents in other staple crops consumed on daily basis using plant-breeding (also known as biofortification) methods. However, developing Ca-biofortified finger millet to reach nutritional acceptability faces various challenges. These include identifying and translating the high grain Ca content to an adequately bioavailable form so as to have a positive impact on Ca malnutrition. In this review, we assess some recent advancements and challenges for enrichment of its Ca value and present possible inter-disciplinary prospects for advancing the actual impact of Ca-biofortified finger millet.